Vocational Students’ Preferences toward Online English Language Learning and Teaching during the Covid-19 Pandemic - Boni Saputra; Rionaldi rionaldi; Arita Destianingsih (INOVISH JOURNAL, 2023)
the Covid-19 pandemic insists face-to-face learning on campus be switched to online or e-learning. However, radical changes are challenging for both educators and students.. This study aims at finding students’ preferences toward online English Language Learning and teaching during the Covid-19 pandemic. The participants of the study were 54 Language Department students at the State Polytechnic of Bengkalis. The research was conducted in a descriptive method. Data and information were gathered through a 5-point Likert scale Google form survey adapted from Coman, et.al (2020). The questionnaire covered students’ technical condition, students’ technical skills / learning styles, lecturers’ technical skills / teaching styles, student’s ability to assimilate and learn while learning online. The data were analyzed using Statistical analysis application; The Statistical Package for the Social Sciences (SPSS) to provide descriptive statistics. The study discovered that video conference platforms were the most preferable in online learning, and live video conference and discussion on chat/forums were the most favorable ones. It was also found that the satisfaction level toward online learning was low; face-to-face learning is still the most favorable. In addition, improvement on students’ technical condition, students’ technical skills / learning styles, lecturers’ technical skills / teaching styles were still needed. Therefore, appropriate utilization of video conference and forum discussion was a necessity. Finally, it is recommended to provide both lecturers’ and students’ training programs to promote better online learning and teaching.Keywords:Online learning; teaching ; pandemic